2002
DOI: 10.1079/bjnbjn2002522
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of <I>n</I>-3 and <I>n</I>-6 polyunsaturated fatty acids on <I>BRCA1</I> and <I>BRCA2</I> gene expression in breast cell lines

Abstract: Current evidence strongly supports a role for the breast tumour suppressor genes, BRCA1 and BRCA2, in both normal development and carcinogenesis. In vitro observations reported that BRCA1 and BRCA2 are expressed in a cell cycle-dependent manner. Interestingly, differences in the actions of n-3 and n-6 polyunsaturated fatty acids have been observed: while the n-3 polyunsaturated fatty acids have been described to reduce pathological cell growth, the n-6 polyunsaturated fatty acids have been found to induce tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(4 reference statements)
1
15
0
Order By: Relevance
“…Increases in EPA and DHA concentration of PL have been demonstrated to decrease cell proliferation and increase apoptosis, by changes in EGFR/AKT/NFkappaB cell survival pathway or by inducing CD95-mediated apoptosis [2][3][4]15]. EPA, but not DHA, increased with SO treatment in the current study, and this fatty acid has been demonstrated to inhibit human breast cancers both in vitro [1][2][3][4][49][50][51][52] and in vivo [7,50] and induce apoptosis [2,4,53]. DPA was increased with SO treatment by more than threefold in tumorigenic cells.…”
Section: Discussionsupporting
confidence: 49%
“…Increases in EPA and DHA concentration of PL have been demonstrated to decrease cell proliferation and increase apoptosis, by changes in EGFR/AKT/NFkappaB cell survival pathway or by inducing CD95-mediated apoptosis [2][3][4]15]. EPA, but not DHA, increased with SO treatment in the current study, and this fatty acid has been demonstrated to inhibit human breast cancers both in vitro [1][2][3][4][49][50][51][52] and in vivo [7,50] and induce apoptosis [2,4,53]. DPA was increased with SO treatment by more than threefold in tumorigenic cells.…”
Section: Discussionsupporting
confidence: 49%
“…On the contrary PUFAs are generally regarded as safe compounds that are well tolerated and produce few side effects. Their effects on nontumorigenic cells have not been fully elucidated, but some studies suggest that when provided at concentrations that inhibit tumor cell growth, n − 3 PUFA exert little or no cytotoxic effects on normal breast cells [17, 18, 108]. Clinical studies are ongoing to show the DHA-improved outcome of chemotherapy in patients with metastatic breast cancer [109, 110].…”
Section: Discussionmentioning
confidence: 99%
“…For example, linoleic acid has been shown to decrease protein levels of tumor suppressor p53, whereas DHA up-regulated expression of p53 (19, 60). Furthermore, dietary lipids have been shown to affect the expression of the suppressor genes breast cancer susceptibility gene 1 (BRCA1) and BRCA2, two genes implicated repeatedly in breast cancer recurrence (10). Omega-3 LCPUFA increased BRCA1 and BRCA2 mRNA expression (10).…”
Section: Potential Mechanisms Linking Dietary Fat To Cancermentioning
confidence: 99%
“…Furthermore, dietary lipids have been shown to affect the expression of the suppressor genes breast cancer susceptibility gene 1 (BRCA1) and BRCA2, two genes implicated repeatedly in breast cancer recurrence (10). Omega-3 LCPUFA increased BRCA1 and BRCA2 mRNA expression (10). …”
Section: Potential Mechanisms Linking Dietary Fat To Cancermentioning
confidence: 99%